Pengaruh Limbah Abu Ampas Kopi Garut terhadap Kuat Lentur Beton - Sali Marsalina; Eko Walujodjati (Institut Teknologi Garut, 2025)
The development of coffee shop businesses in Garut has contributed to the increase in coffee grounds waste, which can pollute the environment. One of the uses of coffee grounds waste is as a substitute for part of the cement in concrete. Coffee grounds ash contains silica which is pozzolanic in concrete. The purpose of this study was to determine the effect of coffee grounds ash as a partial cement substitute on the flexural strength of concrete. The study was conducted using an experimental method using variations of coffee grounds ash of 3%, 6%, and 9% as a partial cement substitute in concrete with a design quality of K-300 (fc’ 25 MPa) and testing at a concrete age of 28 days. Compressive strength testing was carried out on cube test specimens (15 cm x 15 cm x 15 cm) and flexural strength on beams (10 cm x 18 cm x 60 cm), each with 3 samples per variation. The test was guided by SNI 7656:2012. The results showed that increasing the content of coffee grounds ash reduced the strength of concrete. The average compressive strength of normal concrete is 217.72 kg/cm2, decreasing to 198.20 kg/cm2 with a percentage decrease of (8.96%) at a content of 3%, 182.13 kg/cm2 (16.35%) at a content of 6%, and 150.22 kg/cm2 (31.01%) at a content of 9%. This study shows that although coffee grounds ash has the potential as an environmentally friendly material, its use as a partial replacement of cement in concrete with a content of more than 3% actually weakens the mechanical properties of the concrete. Therefore, further research is needed with a lower substitution content or a combination with other additives to improve concrete performance.